Le bénévolat des jeunes Une forme alternative d'éducation - Cortessis , Sandrine (Seismo, 2019)
What makes young people want to learn, commit and become involved in an activity? This issue is of particular interest to teachers, but also to employers. In order to provide some answers, the authors of this book are interested in a specific population: young people aged 16 to 25 who have freely chosen to get involved in associations as varied as sport, politics, the environment, humanitarian work or events. Based on interviews, this study traces the volunteer careers of some forty young women and men from all social categories. They proudly recall the responsibilities that were entrusted to them very early on in a structured, flexible and benevolent associative world. Their testimonies help to highlight the many learning and skills that the volunteer experience has enabled them to develop.